2018
DOI: 10.1002/glia.23291
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine and HIV‐1 Tat disrupt cholesterol homeostasis in astrocytes: Implications for HIV‐associated neurocognitive disorders in cocaine user patients

Abstract: Cholesterol synthesis and clearance by astrocytes are tightly regulated to maintain constant levels within the brain. In this context, liver X receptors (LXRs) are the master regulators of cholesterol homeostasis in the central nervous system (CNS). Increasing levels of cholesterol in astrocytes trigger LXR activation leading to the transcription of target genes involved in cholesterol trafficking and efflux, including apolipoprotein E, cytochrome P450 enzymes, sterol regulatory binding protein, and several AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 60 publications
3
29
0
Order By: Relevance
“…In particular, lncRNA-U1 significantly decreased BAG3 and BCL-2. This phenomenon is also in consistence with our earlier observation of Tat-induced BAG3 supression 55 . BAG3 is a molecular co-chaperone protein participates in apoptotic inhibition by binding to BCL-2 and forming an anti-apoptotic complex 56 , 57 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, lncRNA-U1 significantly decreased BAG3 and BCL-2. This phenomenon is also in consistence with our earlier observation of Tat-induced BAG3 supression 55 . BAG3 is a molecular co-chaperone protein participates in apoptotic inhibition by binding to BCL-2 and forming an anti-apoptotic complex 56 , 57 .…”
Section: Discussionsupporting
confidence: 92%
“…After seven days, both groups of mice were sacrificed and brains were extracted/dissected into regions of interest (i.e. hippocampus, cerebellum, brain stem, and frontal cortex) 55 . Total RNA was isolated for each brain region using Trizole reagent (Invitrogen, ThermoFisher, Carlsbad, CA), as previously described 55 .…”
Section: Ethics Statementmentioning
confidence: 99%
“…Additional changes we noted uniquely in CA1 pyramidal neurons exposed to HIV-1 Tat include a decrease in whole cell capacitance and a likely directly associated decrease in the membrane time constant, which were observed absent any significant change in membrane resistance. While these effects are less obviously related to the clear trend toward hypoexcitability, it is interesting to note that there is some prior evidence that HIV-1 Tat can alter cholesterol production and lipid metabolism in hippocampal astrocytes and neurons (Cotto et al 2018;Mohseni Ahooyi et al 2018). Similarly, it is worth noting that several lines of evidence suggest that HIV-1 Tat may alter synaptodendritic structure and function via mechanisms that depend on filamentous actin (e.g., see Bertrand et al 2014;Festa et al 2015;Krogh et al 2015), a key cytoskeletal protein that may also be relevant to measurements of whole cell capacitance (Herring et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The use of cocaine increases the risk for becoming infected by HIV and many studies have shown that together, HIV and cocaine exacerbate neurocognitive impairment 31 . Moreover, numerous in vitro and in vivo studies have reported that in combination, Tat and cocaine disrupt signaling cascades in the CNS and that these changes significantly affect functioning of uninfected bystander cells 32 34 . In fact, cocaine promotes viral replication in infected astrocytes 15 .…”
Section: Introductionmentioning
confidence: 99%